The Transcriptional Repressor, MtrR, of the mtrCDE Efflux Pump Operon of Neisseria gonorrhoeae Can Also Serve as an Activator of "off Target" Gene (glnE) Expression - Paul J. T. Johnson; William M. Shafer (MDPI AG, 2015)
MtrR is a well-characterized repressor of the Neisseria gonorrhoeae mtrCDE efflux pump operon. However, results from a previous transcriptional profiling study suggested that MtrR also represses or activates expression of at least sixty genes outside of the mtr locus. Evidence that MtrR can directly repress so-called "off target" genes has previously been reported; in particular, MtrR was shown to directly repress glnA, which encodes glutamine synthetase. In contrast, evidence for the ability of MtrR to directly activate expression of gonococcal genes has been lacking; herein, we provide such evidence. We now report that MtrR has the ability to directly activate expression of glnE, which encodes the dual functional adenyltransferase/deadenylase enzyme GlnE that modifies GlnA resulting in regulation of its role in glutamine biosynthesis. With its capacity to repress expression of glnA, the results presented herein emphasize the diverse and often opposing regulatory properties of MtrR that likely contributes to the overall physiology and metabolism of N. gonorrhoeae.